Epidemiology, clinical characteristics, and management of adults referred to a teaching hospital first seizure clinic. Issue 961 (4th November 2005) - Breen, D P; Dunn, M J G; Davenport, R J; Gray, A J
Abstract : Background: There are scarce data describing the epidemiology, clinical characteristics, and management of adults who suffer a suspected first seizure. Aim: To describe the epidemiology, clinical characteristics, and management of adults with a suspected first seizure who are referred to a teaching hospital first seizure clinic over a one year period. Design: Prospective descriptive study. Methods: Data were collected on consecutive adults referred to the Royal Infirmary of Edinburgh between 4 February 2003 and 10 February 2004. Results: 232 patients were referred to the first seizure clinic. Median age was 32 years; 53% of patients were male. Lower socioeconomic groups were more likely to present with a suspected first seizure. Nineteen per cent of patients were admitted to hospital after their suspected seizure episode. Appropriate driving advice was reported in 64% of cases. Seventy two per cent of patients were offered a first seizure clinic appointment within six weeks of referral. Nine per cent of patients had a subsequent seizure while awaiting review. Fifty two per cent of patients were confirmed as having a first seizure at the clinic, of which 56% were provoked by alcohol, recreational drugs, or sleep deprivation. Electroencephalography and computed tomography of the brain were the most common investigations ordered at the first seizure clinic (22% and 22% of patients respectively). Conclusion: Adults who suffer a suspected first seizure, and who make a full neurological recovery, can be safely managed as an outpatient. Around half of these patients will have a specialist diagnosis of first seizure and alcohol will be a common precipitating factor.